MULTIDIMENSIONAL PERSPECTIVES ON CLIMATE CHANGE MITIGATION AND ADAPTATION: A SYNTHESIS OF ECONOMIC, SOCIAL, AND ENVIRONMENTAL STRATEGIES - Tutut Alamin; Pradhita Nurika Ramadani; Rahadian Bayu Riandana; Nadratul Aini; Navy Jihan (PT. Radja Intercontinental Publishing, 2026)
Climate change presents a multifaceted global challenge requiring comprehensive strategies across economic, social, and environmental dimensions. This study aims to synthesize recent research findings regarding climate change mitigation and adaptation strategies, ranging from corporate governance and economic modeling to grassroots agricultural innovations and psychological responses. A comprehensive literature review method was employed to analyze nine recent scholarly articles focusing on diverse aspects of the climate crisis. The synthesis reveals three key themes: (1) The critical role of corporate governance, including board diversity and accounting standards, in managing climate risk; (2) The necessity of technological and policy interventions in agriculture and urban planning to mitigate heat and ensure food security; and (3) The significant impact of psychological and health factors, where emotional responses to climate change drive pro-environmental behavior. The study concludes that effective climate action requires an integrated approach that combines high-level policy frameworks with community-based innovations and psychological engagement .